1
$\begingroup$

Suppose $z=u+iv$, with $v>0$.

$$ m(z)=\dfrac{-z+\sqrt{z^2-4}}{2}$$ satisfies the equation $$m(z)+1/m(z)+z=0 $$ from which we found that $$|m(z)|=|m(z)+z|^{-1} $$

Take the branch of the square root so that the imaginary part of $m(z)$ is postive.

($m(z) $ here is the Stieljes Transformation of the Semicircle Law)

How do we show $$|m(z)|\le 1 $$ or equivalently $$|m(z)+z|\ge 1 $$


As pointed out by Conrad in the comment,$$|m(z)(z+m(z))|=1 $$If we can show $m(z)$ is the smaller of the two in norm, then we are done.

Noting that $$v>0,\qquad m(z)=\dfrac{-z+\sqrt{z^2-4}}{2},\qquad m(z)+z= \dfrac{z+\sqrt{z^2-4}}{2}$$

we have $$Im[m(z)+z] >Im[m(z)] $$ but how about the real part?


as shown in the first few lines of the accepted solution, by the constrains we have on the imaginary part of $z$ and $m(z)$. we have that the real and imaginary part of $$z$$ and $$\sqrt{z^2-4}$$ are of the of the sign. With this we can conclude that $$|m(z)+z|\ge |m(z)| $$

$\endgroup$
  • $\begingroup$ $\sqrt {z^{2}-4}$ has two values (unless $z^{2}=4$). The validity of your inequality depends on how you choose the square root. For example if $z=2i$ then inequality is not true for one of the choices of square root, $\endgroup$ – Kabo Murphy Nov 8 at 12:48
  • 1
    $\begingroup$ $m_1(z) m_2(z)=1$ so in general one of them will have an absolute value less or equal to one and the other greater or equal to one, so obviously there will be a good choice and a bad choice (except in the case where both have absolute value $1$) -maybe the question is not written here complete as you have a given choice and you need to show that works $\endgroup$ – Conrad Nov 8 at 13:30
  • $\begingroup$ Both tags seen unfit for your question, please read tag descriptions first. $\endgroup$ – Viktor Glombik Nov 8 at 15:20
0
$\begingroup$

Let $z=a+ib,\sqrt{z^2-r^2}=c+id$ where $a,b,c,d$ are real and $r>0$

$$r^2=z^2-(z^2-r^2)=(a+ib)^2-(c+id)^2=a^2+d^2-b^2-c^2+2i(ab-cd)$$

Equating the imaginary parts, $ab-cd=0\implies\dfrac ac=\dfrac db=k$(say)

$\implies a=ck,d=bk$

Equating the real parts, $$r^2=a^2+d^2-b^2-c^2=(b^2+c^2)(k^2-1)$$

$\implies k^2-1=\dfrac{r^2}{b^2+c^2}>0$

$\implies$ either $k>1$ or $k<-1$

$$|-z+\sqrt{z^2-r^2}|^2=|c+id-(a+ib)|^2=(c-a)^2+(d-b)^2=(b^2+c^2)(1-k)^2$$

$$=\dfrac{r^2(1-k)^2}{(k^2-1)}=\dfrac{r^2(k-1)}{k+1}$$ which will be $\le r^2$

$\iff\dfrac{k-1}{k+1}\le1\iff0\ge\dfrac{k-1}{k+1}-1=-\dfrac2{k+1}$ $\iff 0\le\dfrac2{k+1}\iff k+1>0\iff k>-1$

So, the proposition will be nullified if $k<-1$

$\endgroup$
  • $\begingroup$ by assumption $b>0$, and the square root is defined to make $Im(m(z)>0)$ which implies $d>0$, so $d/b>0$. $\endgroup$ – a point in Standard Students Nov 9 at 20:35
  • $\begingroup$ but $a/c=d/b>0 $ solves my problem $\endgroup$ – a point in Standard Students Nov 9 at 20:36
-1
$\begingroup$

Let's write $m_1,m_2$ the 2 roots of the equation $m^2+zm+1=0$ where $\Im m_1 \ge 0$ so $m_1=m(z)$ in the post notation.

We know that $m_1=re^{i\theta}, 0 \le \theta \le \pi$, so $\sin \theta \ge 0$ while then $m_2=\frac{1}{r}e^{-i\theta}$, so $0>-\Im z =\Im (m_1+m_2)=(r-\frac{1}{r})\sin \theta$ hence $r-\frac{1}{r} \le 0$ and we are done!

$\endgroup$
  • $\begingroup$ $m_2$ will be the conjuagte of $m_1$, if this is the case shouldn't $m_2=re^{-i\theta}$ $\endgroup$ – a point in Standard Students Nov 9 at 19:28
  • $\begingroup$ @a point no that is not true since $z$ is not real so the roots are not conjugate $\endgroup$ – Conrad Nov 9 at 21:14
  • $\begingroup$ @ Conrad I see. The part I don't understand is why $m_2=\dfrac{1}{r}e^{-i\theta}$, $m_2=m_1^{-1}$ $\endgroup$ – a point in Standard Students Nov 9 at 21:17
  • $\begingroup$ $m_1m_2=1$ by the usual viete relations (roots monic quadratic with free term $1$ $\endgroup$ – Conrad Nov 9 at 23:16

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.